Novel PD-L1- and collagen-expressing patient-derived cell line of undifferentiated pleomorphic sarcoma (JBT19) as a model for cancer immunotherapy - Taborska, Pavla; Lukac, Pavol; Stakheev, Dmitry; Rajsiglova, Lenka; Kalkusova, Katerina; Strnadova, Karolina; Lacina, Lukas; Dvorankova, Barbora; Novotny, Jiri; Kolar, Michal; Vrana, Milena; Cechova, Hana; et al. (Scientific reports, 2023)
Soft tissue sarcomas are aggressive mesenchymal-origin malignancies. Undifferentiated pleomorphic sarcoma (UPS) belongs to the aggressive, high-grade, and least characterized sarcoma subtype, affecting multiple tissues and metastasizing to many organs. The treatment of localized UPS includes surgery in combination with radiation therapy. Metastatic forms are treated with chemotherapy. Immunotherapy is a promising treatment modality for many cancers. However, the development of immunotherapy for UPS is limited due to its heterogeneity, antigenic landscape variation, lower infiltration with immune cells, and a limited number of established patient-derived UPS cell lines for preclinical research. In this study, we established and characterized a novel patient-derived UPS cell line, JBT19. The JBT19 cells express PD-L1 and collagen, a ligand of the immune checkpoint molecule LAIR-1. JBT19 cells can form spheroids in vitro and solid tumors in immunodeficient nude mice. We found JBT19 cells induce expansion of JBT19-reactive autologous and allogeneic NK, T, and NKT-like cells, and the reactivity of the expanded cells was associated with cytotoxic impact on JBT19 cells. The PD-1 and LAIR-1 ligand-expressing JBT19 cells show ex vivo immunogenicity and effective in vivo xenoengraftment properties that can offer a unique resource in the preclinical research developing novel immunotherapeutic interventions in the treatment of UPS.
Keywords: Ligands; myši nahé; Humans; ligandy; sarkom; Mice, Nude; lidé; Immunotherapy; zvířata; myši; B7-H1 Antigen; Mice; buněčné linie; Sarcoma; Cell Line; maligní fibrózní histiocytom; Animals; Histiocytoma, Malignant Fibrous; antigeny CD274; imunoterapie